2012
DOI: 10.1182/blood.v120.21.3123.3123
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outcomes in Multiple Myeloma Using Risk Stratified Allocation to Single Versus Tandem Autologous SCT.

Abstract: 3123 Background: Multiple myeloma (MM) is a plasma cell malignancy with variable prognosis depending on disease features such as β2m level and cytogenetics. High dose therapy and stem cell transplantation (SCT) remains the current standard of care for MM, however the role of tandem SCT is controversial, particularly in the era of novel induction therapy. Methods: The Virginia Commonwealth Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Of note, a recent single-center report described a similar approach and observed that highrisk patients undergoing tandem transplantation had outcomes similar to standard-risk patients undergoing a single ASCT. 34 In the future, consolidation with a 3-drug combination, analogous to the approach of Cavo and colleagues, would ideally be integrated into therapy, particularly in the high-risk setting. Regardless of the choice of induction and post-ASCT regimens, the goal should be a median PFS of 3 or more years, in keeping with the results of the phase III trials discussed above.…”
Section: Post-asct Therapymentioning
confidence: 99%
“…Of note, a recent single-center report described a similar approach and observed that highrisk patients undergoing tandem transplantation had outcomes similar to standard-risk patients undergoing a single ASCT. 34 In the future, consolidation with a 3-drug combination, analogous to the approach of Cavo and colleagues, would ideally be integrated into therapy, particularly in the high-risk setting. Regardless of the choice of induction and post-ASCT regimens, the goal should be a median PFS of 3 or more years, in keeping with the results of the phase III trials discussed above.…”
Section: Post-asct Therapymentioning
confidence: 99%